Reverse cardiac remodeling after transcatheter treatment of severe tricuspid regurgitation using the edge-to-edge mitra clip technique - Ledwoch, Jakob; Fellner, Carmen; Poch, Felix; Schlatterbeck, Leonhard; Dommasch, Michael; Dirschinger, Ralf; Stundl, Anja; Laugwitz, Karl Ludwig; Kupatt, Christian; Hoppmann, Petra (J INVASIVE CARDIOL, 2019)
Objectives. In recent years, transcatheter treatment techniques for tricuspid regurgitation (TR) have rapidly evolved. Cardiac remodeling analysis beyond clinical outcome assessment following transcatheter tricuspid repair is still lacking. The aim of the present case series was to analyze cardiac remodeling after tricuspid valve repair using the edge-to-edge MitraClip technique. Methods. Echocardiographic analysis was performed prior to MitraClip implantation and at 3-month and 6-month follow-up exams. Results. Six consecutive patients undergoing MitraClip implantation between April 2017 and March 2018 at our institution were enrolled. During follow-up, TR reduction was durable in all patients, without recurrence of severe TR. Compared to baseline, right ventricular function improved in 5 out of 6 patients. Reduction in right ventricular area was observed in the majority of patients and reduction in right atrial volume was observed in all subjects. Patients also experienced beneficial left cardiac remodeling. Conclusion. The present series indicates that transcatheter treatment of severe TR using the edge-to-edge MitraClip technique can lead to reverse cardiac remodeling, which is not commonly seen in surgically treated patients.
CRIS-Team Scopus Importer:2023-03-08
Keywords: MitraClip; Reverse remodeling; Transcatheter tricuspid repair; Tricuspid regurgitation